SISTEM INFORMASI PENGELOLAAN PERSEDIAAN BAHAN BAKU BERBASIS CLIENT SERVER PADA CV. ALINEA JAVA SEMARANG - Retno Lestianawati; Rini Rubhiyati (UNIVERSITAS STEKOM, 2018)
Abstract The management of raw material inventory is a very important part for a company. In the process of inventory management of raw materials conducted on CV.Alinea Java until now still using conventional system using Microsoft Excel 2007, starting from material estimation, ordering process of goods to supplier, process of receipt and expenditure of raw materials, raw material returns, addressed to the leadership and related sections. And the utilization of wireless networks that are less effective because only connected computer warehouse administration and purchasing, not all users, to overcome the above problems, it is necessary information that utilizes the inventory management information system raw materials with computer network based client server using a new system of mutual terintregrasi all users so that all interested parties can access the desired data of course with certain restrictions, according to the status entered. Then created a system of inventory management information raw materials server client base on CV.Alinea Java by using Microsoft Visual Basic 6.0 and Microsoft SQL Server 2000 database that will assist in the process of data processing system.